Vertex-Fed Hexagonal Antenna with Low Cross-Polarization Levels - Abhishek Joshi; Rahul Singhal (Advances in Electrical and Electronic Engineering, 2019)
Probe-fed hexagonal patch antenna suffers from impedance mismatch especially when feed is located at one of the vertices of polygon. Hexagonal planar antennas also suffer from high cross polar levels. This paper proposes a method to overcome impedance mismatch and to increase co-polarization level by reducing ground plane. Vertex feeding is demonstrated in this paper to establish improvement in impedance values more clearly. The impedance at any vertex of a hexagonal patch is too high when compared to the characteristic impedance of the probe. Three vertex-fed hexagonal antennas are developed to demonstrate the effect of ground plane reduction within C-Band. The proposed technique can be optimized to match the impedance and achieve good return loss where monopole radiation characteristics are not an issue. A vertex-fed reduced ground hexagonal antenna is proposed here that operates around 5 GHz with a frequency span of 600 MHz. Thus, the proposed antenna is quite suitable for indoor wireless LAN (UNII-1) applications.